The Reported Side Effects of Corona Virus Vaccination among Oral Health Care Workers - Tania Naveel, Remus Chunda (Pakistan Journal of Medical & Health Sciences, 2022)
Vaccines function via a variety of methods to provide disease protection; nevertheless, the process of establishing immunity may create side effects. As a result, the goal of this research was to investigate the COVID–19 vaccination’s acute side effects among oral health care professionals. In order to investigate the pictured objectives the research was conducted in a explorative manner. The data was collected from the oral health care workers using survey analysis to bring insights into the study objectives. Study followed by the descriptive and frequency analysis of the reported side effects in the selected population. The analytical procedures found that persons who have been vaccinated may display a variety of symptoms, and it is important to examine which vaccination is most cost-effective or has the fewest side effects for a certain age range. Classification should be based on these factors. There are many more aspects to consider when making vaccination decisions, including cost-effectiveness, minimal or zero adverse effects, and efforts to protect socioeconomically disadvantaged populations, as well as the urgent need to restore economic and social normality.